Modulation of circularly polarized luminescence through excited-state symmetry breaking and interbranched exciton coupling in helical push–pull organic systems. Issue 2 (29th November 2019) - Dhbaibi, Kais; Favereau, Ludovic; Srebro-Hooper, Monika; Quinton, Cassandre; Vanthuyne, Nicolas; Arrico, Lorenzo; Roisnel, Thierry; Jamoussi, Bassem; Poriel, Cyril; Cabanetos, Clément; Autschbach, Jochen; Crassous, Jeanne
Abstract : Solvent polarity effect on circularly polarized luminescence intensity was assessed in helical push–pull organic systems through excited-state symmetry breaking and interbranched exciton coupling. Abstract : π-Helical push–pull dyes were prepared and their (chir)optical properties were investigated both experimentally and computationally. Specific fluorescent behaviour of bis-substituted system was observed with unprecedented solvent effect on the intensity of circularly polarized luminescence (CPL, dissymmetry factor decreasing from 10 −2 to 10 −3 with an increase in solvent polarity) that was linked to a change in symmetry of chiral excited state and suppression of interbranched exciton coupling. The results highlight the potential of CPL spectroscopy to study and provide a deeper understanding of electronic photophysical processes in chiral π-conjugated molecules.